THE EXISTENCE OF TRANSMIGRATION SETTLEMENT IN THE VILLAGE (a Case in Transmigration Settlement in Mulawarman Village, Kutai Kartanegara Regency) - ANSYAH, JUM (Advances in Social Sciences Research Journal, 2018)
Transmigration settlement is an integral part in the implementation of transmigration programme. The existence of transmigration settlement in a village, including at Mulawarman Village, is the responsibility of the local government as the implementer of transmigration program in regency/city scale in supporting and preserving the settlement to become a settlement that is feasible for a place to live, for work, and for development. The existence of transmigration settlement, in reality, still becomes the main problem for transmigration community to obtain better life since the role of local government as a regulator has not maximal in making policy related to transmigration settlement as well as their role as a facilitator in creating physical development to support all activities conducted by the transmigration community and their role as a dynamic driving forces to drive the aspiration of the transmigration community. Therefore, the existence of transmigration settlement in the village is endangered.